Early-life Famine Exposure, Hunger Recall and Later-life Health - Zichen Deng; Maarten Lindeboom (Tinbergen Institute, 2021)
We use newly collected individual-level hunger recall information from the China Family Panel Survey to estimate the causal effect of undernourishment on later-life health. We develop a Two-Sample Instrumental Variable (TSIV) estimator that can deal with heterogeneous samples. We find a non-linear relationship between the Great Chinese Famine and hunger recall. The non-linearity in famine exposure may explain the variation in the famine's effect on later life health found in previous studies. We also find that exposure to famine-induced hunger early in life leads to worse health among females fifty years later. This effect is larger than the reduced-form effect found in previous studies. For males, we find no impact.
Keywords: I12; J11; C21; C26; 330; famine; hunger; developmental origins; two-sample instrumental variable